AIDS and agriculture in Zambia - Byron, Elizabeth; Chapoto, Antony; Drinkwater, Michael; Gillespie, Stuart; Hamazakaza, Petan; Jayne, Thomas S.; Kadiyala, Suneetha; McEwan, Margaret; Samuels, Fiona (SAGE Publications, 2007)
Background. Because agriculture is the livelihood base for the majority of people affected by AIDS in sub-Saharan Africa, the interactions between AIDS and agriculture, and their implications for policy and programming, are of fundamental importance. Objective. This paper summarizes evidence from three RENEWAL (Regional Network on AIDS, Livelihoods, and Food Security) research studies and one policy review on the interactions between AIDS and agriculture in Zambia and their implications for future policy and programming. Methods. The unit of analysis adopted for each study varies, spanning the individual, household, cluster, and community levels, drawing attention to the wider socioeconomic landscape within which households operate. Results. This paper identifies the ways in which livelihood activities, within the prevailing norms of gender, sexuality, and perceptions of risk in rural Zambia, can influence susceptibility to HIV, and how the nature and severity of the subsequent impacts of AIDS are modified by the specific characteristics and initial conditions of households, clusters, and communities. Conclusions. The findings demonstrate the importance of studying the risks, vulnerabilities, and impacts of the AIDS epidemic in the context of multiple resource flows and relationships between and within households—and in the context of other drivers of vulnerability, some of which interact with HIV and AIDS. The paper addresses several factors that enable or hinder access to formal support programs, and concludes by highlighting the particular importance of engaging communities proactively in the response to HIV and AIDS, to ensure relevance, sustainability, and scale.